Acute Secondary Bacterial Peritonitis due to Perforated Viscera - Mohammad Iqbal Khan, Ahmed Rehman, Naveed Mufti, Afsheen Zafar, Sulman Najam Sheen, Nadir Mehmood and Mohammad Luqman Alvi, (Journal of Rawalpindi Medical College, 2010)
Background: Mortality and morbidity in patients with severe Acute Secondary Bacterial Peritonitis (ASBP), due to perforation of hollow viscera, remains high. Some of these patients develop complications, intra-abdominal as well as systemic, which may contribute to increase hospital stay and death. Methods: Cross Sectional Study; Total number of 118 patients, of ASBP were operated in emergency. Cause of ASBP, location of perforation, timing of presentation and surgery and morbidity and mortality were documented. Results: Duodenal perforation (43.2%) was the commonest, followed by enteric perforations (29.66%), appendicular perforations (13.56%), colonic perforations (7.63%) and gastric perforations (5.93%). Wound infection (14.4%) was the commonest post operative complication. Forty two (35%) patients developed complications requiring prolonged hospital stay. Twenty two (16.64%) patients received total parenteral nutrition, 29 (24.58%) required blood transfusions and ventilatory support was provided to 11 (9.32%) patients. The overall mortality was 5.93%. Seven patients (6%) died in the post operative period. Mortality was highest (33.33%; 3/9) in colonic perforation The bacterial growth was obtained in 102 (91.89%) aspirated samples. Conclusion: High level of suspicion, preventive measures, early recognition and aggressive treatment of developed complications is the hallmark to reduce mortality and morbidity in these patients.